Clinical, Epidemiologic and Ethical Aspects of Hysterectomy in Young Females With Intellectual Disability: A Multi-Centre Study of Public Hospitals in Mexico City - Márquez-González, Horacio; Valdez-Martínez, Edith; Bedolla, Miguel (Frontiers in Public Health, 2021)
Background. Non-therapeutic hysterectomy has been performed to this day in Mexican women with intellectual disabilities (IDs), but the rationale for performing the procedure has been rarely submitted to clinical ethics committees. The objectives of the present research were to determine the frequency of hysterectomy and the clinical and epidemiologic characteristics that associated to the indication of hysterectomy in girls and young females with IDs and to analyse the emerging ethical issues related to the procedure. Materials and Methods. A medical chart review was conducted to identify female patients aged ≤25 years who had IDs based on anatomical pathologies and hospital records and underwent hysterectomy between January 2014 and December 2019 in nine high-concentration hospitals in Mexico City. Data were collected using a questionnaire developed ex professo and validated through a pilot study and analysed using the Statistical Package for the Social Sciences (SPSS) 21.0 software. Results. Information of 234 female patients with or without ID who were ≤25 years of age was reported by the departments of anatomical pathology and paediatrics. Of the patients, 184 (79%) were excluded because the information reported was found to be erroneous or incomplete during the medical records review. Most of the 50 females included in the study had moderate ID (n=23, 46%), followed by those with severe ID (n=17, 34%). The mean age at hysterectomy was 15±2.9 years. Prophylactic-total abdominal hysterectomy was the most frequently performed (n=42, 84%). A concurrence was observed between the parental and medical reasons justifying hysterectomy. The most frequent reasons were fertility control (parents vs physicians: 46% vs 42%), management of menstrual hygiene (28% vs 30%) and risk of sexual abuse (6% vs 6%). Conclusion. This study showed that performing non-therapeutic hysterectomy is subject to the clinical judgement of physicians according to their perception of the patient’s quality of life. Therefore, the ethical quality of the decision to perform the procedure in girls and young females resides in the ethical value of its consequences.